Evaluation of Epidemiological Features and Clinical Symptoms in Patients with Silicosis Hospitalized in Educational and Medical Centers of Hamadan, Iran, From 2011 to 2021 - Mohammad Taha Kouchaki; Sogand Sheikholeslami; Effat Sadat Mirmoeini; Ali Fathi Jozdani; Erfan Ayyoobi; Zohreh Kahramfar; Ali Poormohammadi (Muhandisī-i bihdāsht-i ḥirfah/ī)
Background and Objective: Due to the presence of many workshops related to the production of industrial silica in Hamadan province, the workers in these units are constantly exposed to the risks of inhaling crystalline silica dust. Therefore, the present study aimed to investigate the epidemiological characteristics of patients with silicosis in Hamadan province in Iran. Materials and Methods: An observational cross-sectional study was conducted on 25 patients with silicosis between 2011 and 2021. The study examined the files of all silicosis patients hospitalized in Hamadan hospitals. In this work, the data collection tool included a researcher-made checklist containing eight question sections. Results: According to the results obtained, among 25 patients examined, 4, 4, 5, 6, and 2 were mine workers, stone cutters, stone crushers, glass and silica factory workers, and well diggers, respectively. In addition, 52% of silicosis patients were suffering from cardiovascular diseases, and 20% of the silicosis patients had kidney failure. Conclusion: The results of the present study indicated that people working in silica mines and workhouses are at a higher risk of contracting irreversible silica disease, which highlights the importance of annual and periodic monitoring of exposure to free crystalline silica in their occupations, as well as to control and reduce exposure through the installation of dust control devices. Moreover, in some cases, simple humidification methods and the careful use of personal protective equipment are recommended.